2012
DOI: 10.1136/bmj.e3732
|View full text |Cite|
|
Sign up to set email alerts
|

Effectiveness of home based early intervention on children's BMI at age 2: randomised controlled trial

Abstract: Objective To assess the effectiveness of a home based early intervention on children's body mass index (BMI) at age 2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
352
4
6

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 251 publications
(373 citation statements)
references
References 35 publications
9
352
4
6
Order By: Relevance
“…For example, the proportion of mothers without a university education was 46% in the InFANT trial [44] and 42% in the NOURISH Trial [45]. However a home visiting trial in disadvantaged communities, managed to recruit three quarters of participants without a university education [46]. Surprisingly, we found no difference in the education levels of mothers when recruited by primary health care practitioners in disadvantaged communities and those recruited via social media [40].…”
Section: Discussioncontrasting
confidence: 47%
“…For example, the proportion of mothers without a university education was 46% in the InFANT trial [44] and 42% in the NOURISH Trial [45]. However a home visiting trial in disadvantaged communities, managed to recruit three quarters of participants without a university education [46]. Surprisingly, we found no difference in the education levels of mothers when recruited by primary health care practitioners in disadvantaged communities and those recruited via social media [40].…”
Section: Discussioncontrasting
confidence: 47%
“…Paul et al 49 reported a significant effect on weight-for-length percentiles at 12 months of age (33rd vs 50th, retention 69%; n = 22 vs 30) of an intervention comprising 3 nurse home visits targeting soothing strategies and process of solid introduction. Two other large Australian trials 47,48 have reported outcomes at ∼2 years of age. The Healthy Beginnings Trial 48 evaluated 6 nurse home visits during the first 2 years of life.…”
Section: Figurementioning
confidence: 99%
“…Since the Ciampa review, 24 only 3 [47][48][49] RCTs have reported weight status after an obesity prevention intervention commencing in infancy. All targeted first-time mothers.…”
Section: Figurementioning
confidence: 99%
“…Participants who dropped out of the program tended to be younger mothers on a lower income with a lower level of education. 1 Key challenges in maintaining retention include, but are not limited to, difficulty contacting and maintaining contact with participants who have transient living arrangements, the time involved conducting face-toface interviews for data collection and the priorities of the research design conflicting with those of the participants. These factors influence the time participants have available to be interviewed and return missed telephone calls or text messages.…”
mentioning
confidence: 99%
“…1,2 The aim was to determine whether a homebased obesity intervention during the first 2 years of life is effective for children at 2, 3.5 and 5 years of age. The details of the results from the 2 year follow up are reported elsewhere, 1,2 and the 3.5-and 5-year follow-up of the trial is still underway.…”
mentioning
confidence: 99%